69. Reduced visual cortical reactivity in migraineurs with a positive family history of migraine. Issue 1 (January 2015) - Coppola, G.; Bracaglia, M.; Di Lenola, D.; Di Ciaccia, G.; Di Lorenzo, C.; Serrao, M.; Parisi, V.; Pierelli, F.
<x xml:space="preserve">Abstract</x> In migraine, the genetic load can be seen as determining, on the one hand, a critical threshold for the disease development, and on the other hand, it may be responsible for interictal nervous system dysfunction. We were aimed at verifying whether a family history of migraine might influence migraineurs' cortical abnormal information processing. We retrospectively collected 109 migraine patients from those reviewed who had visual evoked potentials (VEPs) recordings (6 blocks of 100 sweeps, 15 min of arc cheques, 3.1 repetition rate) and information about parental history of migraine. Neurophysiological data were compared with those of 42 healthy volunteers (HV) without family history of migraine. We recruited 109 migraineurs, 85 with and 24 without a positive family history of migraine. Patients who had one parent affected (mother or father) had significantly lower N75-P100 VEP amplitude blocks overall than those had no parents affected, the latter resulting not different from HV. Lack of VEP N75-P100 amplitude habituation was found in overall migraineurs compared with HV, irrespectively of whether they had a parent affected or not. These findings suggest that familial occurrence of migraine may predispose to a general reduced cortical reactivity to visual stimulation.